2021
DOI: 10.1145/3442678
|View full text |Cite
|
Sign up to set email alerts
|

On the Safety of Mobile Robots Serving in Public Spaces

Abstract: Since 2014, a specific standard has been dedicated for the safety certification of personal care robots, which operate in close proximity to humans. These robots serve as information providers, object transporters, personal mobility carriers, and security patrollers. In this article, we point out the shortcomings concerning EN ISO 13482:2014, which encompasses guidelines regarding the safety and design of personal care robots. In particular, we argue that the current standard is not suitable for guaranteeing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 66 publications
(92 reference statements)
0
12
0
Order By: Relevance
“…These sources include research articles, web pages, and product catalogs, retrieved from online academic databases and web search results on Google and Google Scholar. The findings resulting from this research indicated that standards governing robots in different domains could benefit from improvement in the broadest sense of the word and highlighted specific areas which may require further investigation Salvini et al, 2021).…”
Section: Desktop Researchmentioning
confidence: 88%
See 2 more Smart Citations
“…These sources include research articles, web pages, and product catalogs, retrieved from online academic databases and web search results on Google and Google Scholar. The findings resulting from this research indicated that standards governing robots in different domains could benefit from improvement in the broadest sense of the word and highlighted specific areas which may require further investigation Salvini et al, 2021).…”
Section: Desktop Researchmentioning
confidence: 88%
“…6 Oftentimes, however, these standards are not enacted inclusively and lack representation of affected users. Therefore, developers may comply with legislation that does not frame these developments correctly (Fosch-Villaronga, 2016;Fosch-Villaronga and Virk, 2016;Salvini et al, 2021). However, this encourages us to rethink how we can best identify the need to regulate new technologies.…”
Section: Aligning Robot Development and Regulation: A New Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Although policymakers have started to point out psychological consequences of human-machine interactions, both the HRI literature and the safety standards lack a comprehensive investigation of perceived safety towards an enduring presence of robots sharing a common space with humans [80]. As an example, the European Parliament report [31] considered psychological consequences of HRI: "you (denoting users) are permitted to make use of a robot without risk or fear of physical or psychological harm" (p. 23).…”
Section: Introductionmentioning
confidence: 99%
“…Last, in addition to the acceptance level and the effect of COVID-19, robot proxemic behaviors design is also of great importance, as cleaning robots usually operate near humans. Unlike physical safety, which simply requires the robot not to physically injure humans (Asimov, 2004), human mental safety and comfort demands more from the robot, as it requires not just collision-free robot motions, but also consideration and respect for social norms observed in human-human interaction (Salvini et al, 2021). Proxemics, first defined by Edward T. Hall as the physical and psychological distancing from others (Hall, 1966), is one of the most well investigated social norms in robot proxemic behaviors design (Sisbot et al, 2007;Scandolo & Fraichard, 2011).…”
Section: Introductionmentioning
confidence: 99%